Optimisasi Potensi Remaja melalui Pelatihan Manajemen Organisasi Kepemudaan di Pondok Pesantren Nurul Hidayah Lebak Banten - Saefullah, Asep; Kartini, Etin (Jurnal PKM Manajemen Bisnis, 2024)
Islamic boarding schools are educational institutions that have an important role in developing the potential of teenagers. One effort to optimize the potential of teenagers in Islamic boarding schools is through youth organization management training. This training aims to equip teenagers with the skills and knowledge needed to manage youth organizations effectively and efficiently. This community service activity was carried out at the Nurul Hidayah Lebak Banten Islamic Boarding School. This activity was attended by 33 students who are administrators of organizations in the Islamic boarding school environment. This activity lasted for 2 days, namely on 29 and 30 September 2023. The training participants were very enthusiastic about taking part in this activity. They feel that they have benefited a lot from this training, especially in terms of increasing skills and knowledge in managing organizations in the Islamic boarding school environment.